2018
DOI: 10.1111/1462-2920.14359
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities of decaying Norway spruce follow distinct slope exposure and time‐dependent trajectories

Abstract: Deadwood decay employs a complex metabolism and provides carbon and nutrients for soils. Although being highly diverse, the contribution of the bacterial deadwood colonizing community is underexplored compared with the fungal one. Therefore, we performed an in-field mesocosm study and monitored the bacterial communities in decaying experimental Picea abies wood blocks and their underlying soil on north- and south- exposed slopes in the Italian Alps over a 2-year period. The faster deadwood decay at the south-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
(96 reference statements)
3
24
0
Order By: Relevance
“…In particular, the wood density, indicating the progress of decomposition, showed high variation, ranging from 290 to 470 kg m 23 . This is not surprising, since individual deadwood logs are under the complex influence of the individual history of the microbial community assembly and microclimate conditions, including sun exposure and soil contact (20,21). Both CO 2 production from deadwood and N fixation showed a significant correlation with pH (r = 20.720, P = 0.016 and r = 20.832, P = 0.003, respectively).…”
Section: Resultsmentioning
confidence: 95%
“…In particular, the wood density, indicating the progress of decomposition, showed high variation, ranging from 290 to 470 kg m 23 . This is not surprising, since individual deadwood logs are under the complex influence of the individual history of the microbial community assembly and microclimate conditions, including sun exposure and soil contact (20,21). Both CO 2 production from deadwood and N fixation showed a significant correlation with pH (r = 20.720, P = 0.016 and r = 20.832, P = 0.003, respectively).…”
Section: Resultsmentioning
confidence: 95%
“…N-fixing bacteria such as Sphingomonas or Luteibacter could provide N that is known to be limited in the litter environment, while they could receive secondary metabolites from fungi [50]. This has recently been shown for deadwood colonisation [10] and in the rhizosphere where diazothrophs and mycorrhiza, together, promote the growth of the host plant [53]. Positive interactions between microbial species with different functional roles were reported to affect process rates in soil nutrient dynamics [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has shown that bacterial genomes contain cellulase genes [8] and they are capable of cellulolytic activity [9]. Bacteria could probably dominate the first phase of decomposition, where more soluble compounds are still available [9,10]. Despite a long history of research focusing on the dynamics of litter degradation, the role microbial communities play is still debated, especially regarding their local adaptation to litter inputs.…”
Section: Introductionmentioning
confidence: 99%
“…In deadwood, bacteria and archaea may also contribute to pH changes through the two versions of ammonification: (i) N fixation and (ii) anaerobic assimilatory and dissimilatory nitrite reduction to ammonium ( Stein and Klotz, 2016 ). N fixing bacteria ( Hoppe et al, 2014 , 2015 ; Mäkipää et al, 2018 ; Probst et al, 2018 ) and known bacteria involve in dissimilatory nitrite reduction to ammonium (e.g., Clostridium, Klebsiella ) ( Spano et al, 1982 ; Johnston et al, 2016 ) are detected in conifer and broadleaved deadwood logs. Ammonium in deadwood can be then potentially converted to nitrate via nitrification process, hydrogen (H + ) is released, which can decrease wood pH ( Stein and Klotz, 2016 ).…”
Section: Discussionmentioning
confidence: 99%